The effect of word wall game on biodiversity material on students' learning outcomes and activity - Amalia, Firna; Sugianto, Sugianto; Hamidah, Idah (International Journal of Mathematics and Sciences Education, 2025)
The use of monotonous learning media remains one of the factors contributing to suboptimal learning outcomes and low student engagement. This study aims to determine the effect of using the word wall game as a learning medium on biodiversity material in relation to students' learning outcomes and activity. The research employed a quantitative method with a Post-Test Only Control Group design. The study population consisted of 10th-grade students at MAN 1 Indramayu, with class X4 (23 students) as the control group and class X5 (20 students) as the experimental group, totaling 43 students. Based on demographic data, the participants included 18 male students, 25 female students, and 6 students categorized as older than the typical age for 10th grade. Research instruments included 15 multiple-choice questions to assess learning outcomes and 5 observation statements to measure student activity. The results showed that the average score of the control group (X4) was 7.2, while the experimental group (X5) scored an average of 7.7. A descriptive statistical test and a two-sample t-test yielded a tvalue of 0.06 and a ttable value of 1.69, indicating no statistically significant difference between the groups. However, observational data showed that student activity improved progressively: 20% of students fell into the “very poor” category (statement 1), 40% in “poor” (statement 2), 60% in “fair” (statement 3), 80% in “good” (statement 4), and 100% in “very good” (statement 5). These findings indicate a meaningful increase in student engagement. Therefore, the word wall game learning media can be considered effective in improving both student learning outcomes and classroom activity on the topic of biodiversity.